2004
DOI: 10.1097/00005176-200411000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Invasive and Non-Invasive Tests Diagnosis and Monitoring of Helicobacter Pylori Infection in Children

Abstract: Stool antigen (FemtoLab) and UBT were equally effective in diagnosing and confirming eradication of H. pylori infection in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…The stool antigen test is preferable because it is simple, cheap and comparable to the urea breath test [46,47,48]. If the stool antigen test is positive, eradication treatment may resolve thrombocytopenia and should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…The stool antigen test is preferable because it is simple, cheap and comparable to the urea breath test [46,47,48]. If the stool antigen test is positive, eradication treatment may resolve thrombocytopenia and should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…In this previous study, there were 4.5% of inconclusive results (gray zone), which is similar to the reported on the present study. Recently, it has been developed a new monoclonal stool antigen test, which is at least as accurate as HpSA (97.5% sensitivity and 94.7% specificity) and did not have any gray zone (6).…”
mentioning
confidence: 99%
“…Firstly, it should be mentioned that serological tests are not useful to diagnose active H. pylori infection or monitor eradication therapy (25). In fact, histological examination is the most accurate method to diagnose H. pylori infection in children, although this procedure is invasive and not pleasant and acceptable by children and their families (26).…”
Section: Definite Diagnosis Of Helicobacter Pylori In Children and MImentioning
confidence: 99%
“…Some use polyclonal antibodies which are highly sensitive and specific for the diagnosis of this infection in adults and children. A few studies on children found comparable efficacy between UBT and HpSA (25). Limitations of the HpSA include inter-test and lot-to-lot variability, cutoff values and lower accuracy after eradication therapy.…”
Section: Definite Diagnosis Of Helicobacter Pylori In Children and MImentioning
confidence: 99%
See 1 more Smart Citation